Citizenship and Human Rights Education as a Cross-Curricular Subject: Elementary Students' Views on Human Rights - Bagli, Melike Türkan (Egitim ve Bilim, 2013)
This research aims at exploring how the 7th and 8th graders of 3 elementary schools in Ankara conceptualize human rights and how they perceive human rights and citizenship in the context of their courses and textbooks after the course on "Citizenship and Human Rights Education" was considered as a cross-curricular subject. It also aims at evaluating their views on human rights issues and suggested solutions. The students are interviewed by using focus group methodology. The findings suggest that the students consider courses mentioning human rights and citizenship as "boring", and think that the course content is too familiar and unauthentic. It is observed that the students have acquired basic knowledge on human rights and been aware of human rights issues in Turkey and rest of the world. However, the students are desperate about the solution of these problems. Consequently, human rights education does not seem to serve the purpose of empowering individuals and there is no formation of a holistic perception of human rights in the students' minds. Therefore, "Citizenship and Human Rights Education" as a cross-curricular subject did not seem to help students reaching the goals of human rights education. [PUBLICATION ABSTRACT]